Volunteering as Students significant social activities - I. A. Zaitseva (Проблемы постсоветского пространства)
The article examines the involvement of students in volunteer activities, examines the organization of students volunteer activities and volunteer projects realization at the university. The potential of volunteerism as an effective mechanism for addressing the urgent social problems is revealed.Theauthorstudiesexperience of volunteer services organization the I.A. Bunin State University in Yelets.